2019
DOI: 10.1080/1478422x.2019.1657703
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of a Zr-based conversion coating on galvanised steel and its performance against corrosion

Abstract: New protective coatings with satisfactory performance and low impact are required by the surface treatment industry as effective Cr(VI)-free substitutes. Recently conversion coating systems containing Zr/Ti have shown great promise particularly for zinc finishes on steel and in this paper, we study the influence of bath conditions (e.g. pH and time) on conversion layers composed of a Zr-based film. The coating formation was studied by simultaneous monitoring of open circuit potential and surface pH using a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…But, if this pH is too low, as 2.5, the anodic oxide will be excessively deteriorated, losing part of its capability of protection instead of anchoring the Zr conversion coating, as it was desired. On the other hand, if the pH is higher than necessary, the solution is not acidic enough to slightly dissolve the anodic oxide to initiate the reaction on the surface and, instead, the ZrO 2 will form and precipitate in the solution bulk 27 . This last situation happened to the H 2 ZrF 6 solution with pH 4.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…But, if this pH is too low, as 2.5, the anodic oxide will be excessively deteriorated, losing part of its capability of protection instead of anchoring the Zr conversion coating, as it was desired. On the other hand, if the pH is higher than necessary, the solution is not acidic enough to slightly dissolve the anodic oxide to initiate the reaction on the surface and, instead, the ZrO 2 will form and precipitate in the solution bulk 27 . This last situation happened to the H 2 ZrF 6 solution with pH 4.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…The concentration of H 2 ZrF 6 solution is also important to the usability of the Zr conversion coating over anodized AA7075 alloy. Solutions with low concentrations are commonly utilized directly on other substrates 17,19,27 but have now shown to be inappropriate for being used as a corrosion protective on anodized layers. There are studies evaluating corrosion resistance of different conversion coatings based on Zr applied directly on AA7075 alloy 4,19,28 .…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The samples treated with H 2 ZrF 6 showed the highest corrosion resistance compared to the unsealed aluminum samples. They also applied the same strategy to galvanized steel substrates, proving that the Zr-CCC deposition is highly dependent on the solution pH and on the reaction time [20]. Such pre-treatments have demonstrated to improve both the corrosion resistance and the adhesion of top coats and adhesives [9,10,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…Such coatings, with specific weight of only 0.01 to 0.02 g/m 2 , are extremely thin and represent a great advantage of cost and light-weighting final material for the producers [ 1 ]. The effectiveness of the dip-coating process by immersion of the metal substrate in hexafluorozirconic-acid-based (H 2 ZrF 6 -based) solution is pH limited and the homogeneity of the obtained films is sometimes poor [ 12 ]. Previous works have demonstrated that the incorporation of auxiliary additives in the bath solutions, like copper (II), nickel (II), nitrate (NO 3 − ) and hydrogen phosphate (HPO 4 2− ) ions, are necessary to further improve the barrier property and the density of Zr-CCC layer [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%